The Michigan Critical Care Handbook - Robert H. Bartlett (Critical Climate Change, 2010)
From the introduction: "[The Michigan Critical Care Handbook] is truly a handbook. It contains no prose, only charts, tables, diagrams, and algorithms necessary for monitoring and managing critically ill patients. Background, discussion, and detailed references are presented in the Critical Care Physiology text."